Comparison of performance of F1 Romanov crossbred ewes with wool and hair breeds during spring lambing under intensive and extensive production systems - Freking, Brad A (J Anim Sci, 2020)
The objective was to evaluate wool (Dorset and Rambouillet) and hair (Dorper, Katahdin, and White Dorper) breeds for their ability to complement Romanov germplasm in two distinct production systems by estimating direct sire and grandsire effects on lamb growth, survival, and ewe productivity traits. Rams of the five breeds (n = 75) were mated to Romanov ewes (n = 459) over a 3-yr period to produce five types of crossbred lambs (n = 2,739). Sire breed (P > 0.06) did not impact body weight or survival traits of the first-generation crossbred (F1) lambs. The productivity of retained crossbred ewes (n = 830) mated to Suffolk and Texel terminal sires was evaluated at 1, 2, and 3 yr of age in each production system. In the intensive production system, labor and harvested feed were provided for sheep that lambed in March in barns, and ewes were limited to rearing two lambs with additional lambs reared artificially. Ewes in the extensive production system lambed in May on pasture and were responsible for rearing all lambs born with no labor or supplemental feed provided before weaning. A total of 1,962 litters and 4,171 lambs from 2,229 exposures to two terminal sire breeds (Suffolk and Texel) were produced in the experiment. Crossbred ewes in the intensive production system were mated in October, resulting in larger litter sizes than crossbred ewes mated in December for the extensive production system. However, single- and twin-born lamb mortality was similar between the two systems that differed greatly in labor, feed, and facilities. Lambs produced in the intensive system received concentrate feed from an early age and were heavier at 24 wk of age than lambs produced in the extensive system. These outcomes resulted in greater 24-wk litter weight in the intensive than in the extensive system (P < 0.0001). Unexpectedly, the relative performance of crossbred types did not differ importantly between production systems. White Dorper × Romanov crossbred ewes had numerical advantages in productivity in each system; however, differences between ewe types were not significant. In the extensive system, without labor and shelter at lambing or supplemental feed until weaning, 3-yr-old crossbred ewes of all types averaged 1.78 lambs marketed per ewe lambing, and 40% of the ewes that gave birth to triplets weaned their entire litters. These results document that prolific sheep and extensive systems can be successfully combined if appropriate crossbred types are used.